Reverse microemulsion synthesis of monodispersed square-shaped SnO2 nanocrystals - Yu, C.; Zhou, W.; Yang, K.; Li, L.; Chao, F.; Li, Xin Yong (2010)
A nanosized reverse microemulsion reactor was designed for the fabrication of monodispersed SnO2 nanosquares by oxidation of SnF2 under hydrothermal conditions. As-prepared samples were characterized by X-ray diffraction, scanning electron microscope, transmission electron microscope and high resolution transmission electron microscope. The results show that the morphology of the SnO2 nanocrystals can be controlled by regulating the amount of the used oleylamine which direct influenced the pH values of the aqueous phase. Well monodispersed SnO2 nanosquares with the size around 10 nm can be obtained. A proper pH value could benefit the oriented attachments of the crystalline seeds which gradually grew into a square-plate NCs shape in the microemulsion reactor.